2014
DOI: 10.1002/uog.13351
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of cardiovascular parameters in twin‐to‐twin transfusion syndrome

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
4
29
1
Order By: Relevance
“…In seven studies, echocardiographic findings were analyzed in relation to IUFD . We could only perform a meta‐analysis on atrioventricular regurgitation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In seven studies, echocardiographic findings were analyzed in relation to IUFD . We could only perform a meta‐analysis on atrioventricular regurgitation.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies assessed the preoperative myocardial performance index (MPI) as a separate parameter, of which two report an increased risk of recipient demise . In a study of 105 recipients, the risk of recipient demise was four times higher if the MPI z score was above a cutoff z score of 1.645, which corresponds to the 95th percentile (p < .01). After adjustment for gestational age and placental localization, there was no increased risk (OR 3.09, 95% CI, 0.94‐9.30, p = .06).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increases in ICT and IRT but not ET can be interpreted as myocardial impairment of both contraction and relaxation with shortening of the diastolic filling time. Although several studies have evaluated cardiac dysfunction in recipients using Mod‐MPI, only a few reports have assessed its components, mainly focusing on the diastolic function . Divanović et al reported increased IRT in recipients, and this change was more significant in advanced‐stage TTTS .…”
Section: Discussionmentioning
confidence: 99%